To find the compositions of the functions \( f(x) \) and \( g(x) \), we will first recall the definitions:
\[ f(x) = \frac{8x - 9}{6} \] \[ g(x) = \frac{6x + 9}{8} \]
(a) Find \( (f \circ g)(x) \)
This means we need to find \( f(g(x)) \).
- Calculate \( g(x) \):
\[ g(x) = \frac{6x + 9}{8} \]
- Substitute \( g(x) \) into \( f(x) \):
Now, substitute \( g(x) \) into \( f(x) \):
\[ f(g(x)) = f\left(\frac{6x + 9}{8}\right) = \frac{8\left(\frac{6x + 9}{8}\right) - 9}{6} \]
- Simplify the expression:
\[ = \frac{(6x + 9) - 9}{6} = \frac{6x}{6} = x \]
Thus,
\[ (f \circ g)(x) = x \]
(b) Find \( (g \circ f)(x) \)
Now we need to find \( g(f(x)) \).
- Calculate \( f(x) \):
We already have \( f(x) \):
\[ f(x) = \frac{8x - 9}{6} \]
- Substitute \( f(x) \) into \( g(x) \):
Now substitute \( f(x) \) into \( g(x) \):
\[ g(f(x)) = g\left(\frac{8x - 9}{6}\right) = \frac{6\left(\frac{8x - 9}{6}\right) + 9}{8} \]
- Simplify the expression:
\[ = \frac{8x - 9 + 9}{8} = \frac{8x}{8} = x \]
Thus,
\[ (g \circ f)(x) = x \]
Summary
\[ (f \circ g)(x) = x \quad \text{and} \quad (g \circ f)(x) = x \]
Both compositions return \( x \).